Generating Multi‐Carbon Products by Electrochemical CO2 Reduction via Catalytically Harmonious Ni/Cu Dual Active Sites - Lakshmanan, Keseven; Huang, Wei‐Hsiang; Chala, Soressa Abera; Chang, Chia‐Yu; Saravanan, Sruthi Thiraviam; Taklu, Bereket Woldegbreal; Moges, Endalkachew Asefa; Nikodimos, Yosef; Dandena, Berhanu Degagsa; Yang, Sheng‐Chiang; Lee, Jyh‐Fu; Huang, Pei‐Yu; et al. (Small (Weinheim an der Bergstrasse, Germany), 2024)
Despite the unique advantages of single‐atom catalysts, molecular dual‐active sites facilitate the C‐C coupling reaction for C2 products toward the CO2 reduction reaction (CO2RR). The Ni/Cu proximal dual‐active site catalyst (Ni/Cu‐PASC) is developed, which is a harmonic catalyst with dual‐active sites, by simply mixing commercial Ni‐phthalocyanine (Ni‐Pc) and Cu‐phthalocyanine (Cu‐Pc) molecules physically. According to scanning transmission electron microscopy (STEM) and transmission electron microscopy (TEM) energy dispersive spectroscopy (EDS) data, Ni and Cu atoms are separated, creating dual‐active sites for the CO2RR. The Ni/Cu‐PASC generates ethanol with an FE of 55%. Conversely, Ni‐Pc and Cu‐Pc have only detected single‐carbon products like CO and HCOO−. In situ X‐ray absorption spectroscopy (XAS) indicates that CO generation is caused by the stable Ni active site's balanced electronic state. The CO production from Ni‐Pc consistently increased the CO concentration over Cu sites attributed to subsequent reduction reaction through a C‐C coupling on nearby Cu. The CO bound (HCOO−) peak, which can be found on Cu‐Pc, vanishes on Ni/Cu‐PASC, as shown by in situ fourier transformation infrared (FTIR). The characteristic intermediate of *CHO instead of HCOO− proves to be the prerequisite for multi‐carbon products by electrochemical CO2RR. The work demonstrates that the harmonic dual‐active sites in Ni/Cu‐PASC can be readily available by the cascading proximal active Ni‐ and Cu‐Pc sites. Ethanol is produced by a Ni/Cu dual active site in the Ni/Cu‐PASC catalyst. Because of the CO that has migrated from the Ni atom, a harmonious Ni/Cu dual atom site modifies the coordination bind site, converting the Cu‐*OCHO intermediate site to Cu‐*CHO. Ethanol is eventually produced when the Ni/Cu dual site facilitates the C‐C coupling via Cu‐*CHO‐CO .